Sowards Ed. Makers Of World History - Davis, Gerald (Teaching History: A Journal of Methods, 1994)
Among Western Civ teachers, J. Kelley Sowards has been known for a long time as a provider of useful biographical supplements for basic textbooks. Now, as many of us adapt to the demands of World Civ, we have his Makers of World History to perform the same service. In both the Western and World courses, Sowards seems to assign a large role to "great men" and "great women" in the generation of historical forces. This runs against strong trends in basic textbook publishing and other elements of the historical profession that favor "non-elitist social history" and guide readers’ attention toward dynamic processes, groups, and categories.